Transforming Learning Management with Class of Champions: Exploring its Effect on Student Cooperation - Firda Ambar Agustin; Rozy, Fakhrur (Al-Qalam Institue, 2025)
This study examines the impact of the Class of Champions game on student collaboration during Civics Education lessons. Collaboration is key to effective learning, and this research highlights its importance in achieving educational success. Using a quantitative descriptive method with 25 students, the study utilised a collaboration assessment sheet with eight indicators, which was tested for validity and reliability on 28 students. Results showed valid indicators with correlation coefficients ranging from 0.554 to 0.908 and a Cronbach's Alpha of 0.893, indicating high reliability. The analysis revealed that student collaboration was rated as